A81 BARRIERS AND FACILITATORS OF PEDIATRIC TO ADULT TRANSITION IN IBD: A PILOT STUDY EVALUATING THE STAKEHOLDER EXPERIENCE. (4th March 2021) - Chis, R; Jawaid, N; Fu, Y; Bollegala, N
Abstract: Background: Inflammatory bowel disease (IBD) is increasing in prevalence with up to 25% of IBD patients diagnosed before 18 years of age. These patients will require graduation from pediatric care to adult services. The transition of care from pediatric to adult gastroenterologists (GIs) is a purposeful transition that requires planning with involvement of all stakeholders to ensure proper transition and avoid interruption in care. Aims: To identify the transition experiences of adult patients with pediatric diagnoses of IBD, their parents, pediatric and adult GIs and registered nurses (RNs) and identify barriers and facilitators to a successful transition. Methods: Patients aged 18–25 diagnosed with pediatric-onset IBD were included. Semi-structured focus groups were held with 9 patients and separately with 4 parents. Questions focused on the patient transition experience, opportunities for improvement, and patient quality of life. Transition practices and expectations of 12 adult GIs, 7 pediatric GIs and 9 IBD nurses were also investigated in a series of provider specific focus groups. The groups were audio-recorded, transcribed and qualitative themes were noted. Results: Patients: Facilitators included ease of access to adult providers outside of clinic time and parental presence in the early stages of transition. Barriers included abrupt transitions to adult care by age 18, lack of choice regarding adult GI and lack of adult nursing. Parents: Facilitators included an extended transition period, availability of support groups/resources. Barriers related to exclusion from the transition process and lack of input on adult GI choice. RNs: Facilitators include having champion IBD nurses on the pediatric and adult side during transition. Barriers included lack of educational tools for patients. Pediatric GIs: Facilitators included effective communication between adult and pediatric GIs, having an emergency assessment protocol, involving families in the transition process and access to multidisciplinary resources. Barriers included prolonged wait time for transfer and lack of adult access to multidisciplinary support. Adult GIs: Facilitators included succinct transfer summaries and formal transition programs for high risk patients. Barriers included a lack of multidisciplinary support, difficulty reaching rural areas, heavy case loads and prolonged wait time to transfer of care. Conclusions: This study explores the stakeholder experience of pediatric to adult transition in IBD. Themes noted related to efficient communication between GIs, streamlining transfer summaries, ensuring a gradual transition process, involving parents and ensuring access to multidisciplinary resources. Identifying barriers and facilitators during the transition process can provide insight into creating a successful pediatric to adult transitions program in IBD. Funding Agencies: None